OPTIMIZATION OF DANCE EDUCATION THROUGH CREATIVE MEDIA: INTEGRATION OF TEXT, VIDEO, AND AUDIOVISUALS IN THE EDUCATIONAL PROCESS - Budiarsa, I Wayan; Utamia, Dewa Gede Satya Adi Maha; Sari, Ni Wayan Arma Yonika (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
This research is motivated by the need to enhance the effectiveness of dance education, which often faces challenges in conveying movement concepts in a visual and comprehensive manner. The aim of this study is to optimise dance learning through the integration of creative media, including text, video, and audiovisual elements within the educational process. The method employed is qualitative research with a descriptive approach, wherein data are collected through observations, interviews, and document analysis at dance education institutions. The findings indicate that the integration of creative media not only boosts student motivation and engagement in the learning process but also enriches their understanding of dance techniques and aesthetics. Furthermore, audiovisual media have proven effective in clarifying movement representation and strengthening the skill evaluation process. This research recommends the use of creative media as an innovative strategy in dance education in the era of disruption.